Analysis of Code Mixing in Unila Zoom Photography Student Speech - Sri Kartini (Research in Education, Technology, and Multiculture, 2022)
Abstract: This research  was conducted with  the intention  of describing the utterances  used by Unila photography zoom  ukm students. Speeches using different languages will produce various contexts.  This research was reviewed using a descriptive qualitative method. By obtaining data in the form of dialogue between Javanese-speaking students and Indonesian-speaking students, the results  of this  study  will  be  carried out by  describing whether the existing code mixing can make communication between speakers and interlocutors run straight or not according to the goals of the speakers and interlocutors.   Keywords: speech, code mixing, university students.